Development of Luwu Culture Through Interactive Educational Games Based on Android Smartphones by Using Abode Animate CC - Lilis Suryani; Sukmawaty Sukmawaty; Miftha Zulfahmi Muassar; Ahmiranti Ahmiranti (AL-ISHLAH: Jurnal Pendidikan, 2023)
The objective of this study is to create educational game applications using Adobe Animate CC and assess the effectiveness and feasibility of interactive educational games on Android smartphones. This research falls under the Research and Development (RD) category using the Multimedia Development Life Cycle (MLDC) model. The research was carried out on the student population of the Madrasah Ibtidayah Teacher Education study programme at IAIN Palopo for the academic year 2021/2022, which consisted of 87 students. Meanwhile, the trial involved second-semester students who programmed social studies courses Madrasah Ibtidayah/Elementary School, namely a group of 15 students. The data collection methods employed in this study encompassed interviews, observation of validity questionnaires, and practicality questionnaires. The application development process employs the MDLC development paradigm, which encompasses six stages: concept, design, material collection, assembly, testing, and distribution. This study reveals that the utilisation of this application has the potential to enhance students' understanding, particularly in regard to the fundamental aspects of Palopo's culture, as demonstrated by the use of this game. The gaming application was evaluated by experts, who determined that the product's value, as assessed by material specialists, was 94%, indicating that it is suitable for distribution. Media specialists generate a 90% score (very commendable for dissemination). Conversely, the practicality test yielded a 90% (efficient) final score. The practicality test results of 92% indicate a high level of efficiency and are suitable for dissemination.